1997
DOI: 10.2337/diab.46.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation Restores Epinephrine Response and Symptom Recognition During Hypoglycemia in Patients With Long-Standing Type I Diabetes and Autonomic Neuropathy

Abstract: Impaired epinephrine secretion and symptom unawareness are characteristic of severe hypoglycemia in individuals with long-standing type I diabetes. Recently, the avoidance of clinical hypoglycemia has been reported to improve epinephrine and symptom responses to hypoglycemia in type I patients. However, the extent to which these defects can be restored in individuals with long-standing type I diabetes and autonomic neuropathy has not been assessed, nor has it been determined whether pancreas transplantation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 29 publications
2
33
2
3
Order By: Relevance
“…This trial also shows, in contrast to prior studies (1), that protection from SHEs can be achieved without accepting an elevated HbA 1c target. Vascularized pancreas transplantation, which is generally reserved for patients needing a simultaneous kidney transplant (26), is the only other intervention capable of achieving similar results (27,28), but is uncommonly used in nonuremic T1D patients (26). …”
Section: Discussionmentioning
confidence: 99%
“…This trial also shows, in contrast to prior studies (1), that protection from SHEs can be achieved without accepting an elevated HbA 1c target. Vascularized pancreas transplantation, which is generally reserved for patients needing a simultaneous kidney transplant (26), is the only other intervention capable of achieving similar results (27,28), but is uncommonly used in nonuremic T1D patients (26). …”
Section: Discussionmentioning
confidence: 99%
“…Impaired hypoglycemia-induced glucagon secretion has also been observed in subjects receiving an intrahepatic islet autotransplant [38]. This stands in contrast to diabetic patients receiving whole pancreas transplants, in whom restoration of glucagon and epinephrine secretion in response to hypoglycemia has been observed [39][40][41]. Studies in a canine model of islet transplantation demonstrated a similar lack of glucagon response to hypoglycemia following intrahepatic transplantation of islets, whereas glucagon secretion was normal following transplantation of the islets into the peritoneal cavity [42].…”
Section: Metabolic Outcomes Of Human Islet Transplantationmentioning
confidence: 77%
“…Measurements of C-peptide mitigated against this explanation because they fell appropriately during the hypoglycemic clamps, indicating that the intrahepatic islet senses low glucose levels in the blood supplying the transplanted islet. Pilot studies in two islet recipients with type 1 diabetes mellitus also indicated a lack of glucagon responses to insulin-induced hypoglycemia [13]. It should be noted, however, that the degree of hypoglycemia in this trial was minimal, ie, a level of approximately 56 mg/dL.…”
Section: β-And α-Cell Functionmentioning
confidence: 93%
“…Previously, it had been observed that pancreas transplantation successfully restored glucagon responses to insulin-induced hypoglycemia in type 1 diabetic recipients [13]. Therefore, it was expected that successful autoislet transplantation would do the same.…”
Section: β-And α-Cell Functionmentioning
confidence: 98%